2006
DOI: 10.1088/0960-1317/16/2/012
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of multi-layer SU-8 microstructures

Abstract: The fabrication of multi-level SU-8 microstructures using multiple coating and exposure steps and a single developing step has been achieved for up to six layers of SU-8. Alternating layers of SU-8 2010 (thin) and SU-8 2100 (thick) photoresist films were spin coated, followed by soft-bake, ultraviolet (UV) exposure and post-exposure bake steps. The multiple SU-8 layers were simultaneously developed to create patterned microstructures with overall thicknesses of up to 500 µm and minimum lateral feature size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
155
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(157 citation statements)
references
References 41 publications
(93 reference statements)
1
155
0
1
Order By: Relevance
“…On the other hand, geometric structures including rough structures and regular micro/nano patterns are also crucial [13,14]. To obtain polymer regular micro/ nano geometric surfaces, various nanoprocessing approaches can be employed, including nanoporous template wetting [15], capillary lithography [16], nanoimprint lithography [17], microstereolithography [18], template rolling press [19], and water spreading of carbon nanotubes [20]. A number of theoretical and experimental studies indicated that polymer aligned nanopillar arrays or carbon nanotube arrays could exhibit hydrophobic or surperhydrophobic feature [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, geometric structures including rough structures and regular micro/nano patterns are also crucial [13,14]. To obtain polymer regular micro/ nano geometric surfaces, various nanoprocessing approaches can be employed, including nanoporous template wetting [15], capillary lithography [16], nanoimprint lithography [17], microstereolithography [18], template rolling press [19], and water spreading of carbon nanotubes [20]. A number of theoretical and experimental studies indicated that polymer aligned nanopillar arrays or carbon nanotube arrays could exhibit hydrophobic or surperhydrophobic feature [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid excessive stress, adhesion failure, and pattern dimensional change, exposure dose must be adjusted according to the substrate or under layer reflectivity. 16 For this case, finding the optimum dose for the second layer was a serious challenge, because an extra or not sufficient dosage could lead to the pore occlusion and pattern failure. After exposing the second layer, wafer was kept again on the hotplate at 95 C for the FIG.…”
Section: Methodsmentioning
confidence: 99%
“…We utilized SU-8 (MicroChem Corp., Newton, MA) as a potential material for membrane fabrication because it is an epoxy-type photoresist with suitable chemical and mechanical properties that have been used widely for the development of complex features like multi-level microstructures. 15,16 Technically, fabrication of small micro-holes (i.e., 0.5-5 lm) inside a thick SU-8 film is impossible due to the tapering effect, 17,18 which normally happen during UV exposure (i.e., usually top layer is overexposed and tends to be wider than the bottom layer which is relatively underexposed, resulting in the variation of the lateral dimensions). To overcome this impediment, we employed multi-level lithography technique to fabricate polymeric membrane using multiple coating and exposure steps and a single developing process.…”
Section: Introductionmentioning
confidence: 99%
“…2) utilizing multi-layered SU-8 epoxy based negative photoresist [13,14,15] as a master replica for PDMS moulding [3]. The SU-8 layers were patterned by subsequent spin-coatings and lithographic exposures and a final development step.…”
Section: Microfabricationmentioning
confidence: 99%